2015
DOI: 10.1371/journal.pone.0134620
|View full text |Cite
|
Sign up to set email alerts
|

Klf15 Is Critical for the Development and Differentiation of Drosophila Nephrocytes

Abstract: Insect nephrocytes are highly endocytic scavenger cells that represent the only invertebrate model for the study of human kidney podocytes. Despite their importance, nephrocyte development is largely uncharacterised. This work tested whether the insect ortholog of mammalian Kidney Krüppel-Like Factor (Klf15), a transcription factor required for mammalian podocyte differentiation, was required for insect nephrocyte development. It was found that expression of Drosophila Klf15 (dKlf15, previously known as Bteb2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…35 Recent studies in Drosophila revealed that Klf15 is critical for nephrocyte development and differentiation. 36 Combined with our previous work, 15 we show here that the KLF15 is required for DEX-induced restoration of podocyte differentiation markers (i.e., expression of nephrin and synaptopodin and actin stress fiber formation). Podocin-Cre Klf15 flox/flox mice only exhibited approximately 50% knockdown in KLF15 expression, which likely attributed to less severe podocyte injury in the proteinuric murine models compared with the global Klf15 2/2 mice.…”
Section: Discussionsupporting
confidence: 84%
“…35 Recent studies in Drosophila revealed that Klf15 is critical for nephrocyte development and differentiation. 36 Combined with our previous work, 15 we show here that the KLF15 is required for DEX-induced restoration of podocyte differentiation markers (i.e., expression of nephrin and synaptopodin and actin stress fiber formation). Podocin-Cre Klf15 flox/flox mice only exhibited approximately 50% knockdown in KLF15 expression, which likely attributed to less severe podocyte injury in the proteinuric murine models compared with the global Klf15 2/2 mice.…”
Section: Discussionsupporting
confidence: 84%
“…8 In the current issue of the Journal , these groups extend their investigations to address how nephrocytes influence cardiomyocytes. 9 Using dKlf15 NN/NN mutants, that harbor a piggyBac P-element insertion within the coding region of dKlf15 and lack pericardial nephrocytes, the authors observed bradycardia, prolongation of the diastolic period, and increased systolic and diastolic dimensions.…”
mentioning
confidence: 99%
“…The signaling ones encoded 3 homologs of the transcription factor Krüppel (Kr) (Fig 1C). In D. melanogaster , Kr and Kr homologs are involved in several developmental processes such as embryo patterning (71), organogenesis (7274), and cell differentiation (75). More specifically in the hemocytes, Kr has been shown to take part in hemocytes’ differentiation and/or activation (76), a crucial step for the induction of cellular immune responses.…”
Section: Resultsmentioning
confidence: 99%